Identifikasi Komponen Kimia Damar Mata Kucing (Shorea Javanica) dengan Metode Pirolisis-GC/MS - Mulyono, Noryawati; Wijaya, Christofora Hanny; Fardiaz, Dedi; Rahayu, Wuryaningsih Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
The aim of this research was to identify chemical compounds in cat eye dammar. The method included functional groups characterizationby infrared spectrophotometer and identification using Pyrolisis-GC/MS. Infrared spectra of crude sample showed that there were somefunctional groups such as alkyl, carbonyl, vinyl, and hydroxyl. Identification by Pyrolisis-GC/MS showed that dammar consisted of at least67 compounds. This natural gum components could be categorized into 4 groups, i.e. tetra cyclic hydrocarbon (30 compounds, 49.57%),penta cyclic (3 compounds, 2.56%), C 15 compounds (11 compounds, 17.09%), and other group (23 compounds, 18.26%). According to thePy-GC/MS data, brassicasterol is the highest relative concentration in dammar, i.e. 20%.